Synthesis and characterization of potential impurities of ezetimibe. (1st November 2022) - Satheesh, Deekonda; Devi, Dharmasoth Rama; Basavaiah, Keloth; Sreenivasulu, B.; Reddy, Bhavanam Sekhara; Aegurla, Balakrishna; Kumar, Pallerla Satish; Guduri, Anil Kumar; Chavakula, Ramadas
Abstract: Ezetimibe is an azetidinone derivative and a substituted β‐lactam, it is a hypolipidemic agent, and a drug substance that lowers the cholesterol levels in our body. The present work describes the origin, synthesis, and characterization of three impurities of ezetimibe, which are also positional isomers and/or related substances of ezetimibe. viz: o ‐Fluoro benzene isomer, m ‐Fluoro aniline analog, and des ‐fluoro aniline analogs of ezetimibe. Abstract : Synthesis and characterization of potential impurities of ezetimibe.